Functional gradient thermal protection coating and automatic forming method thereof
By using functional gradient design and automatic spraying technology in thermal protection coatings, self-healing, ceramic and carbide layers are formed, which solves the corrosion and deformation problems of single-layer coatings, and improves high temperature stability and thermal protection performance. .
Patent Information
- Application Number
- CN202411327133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The thermal protection coatings of existing single-layer structures are prone to environmental corrosion and inevitable incongruence of expansion and contraction deformation during service, resulting in oxidation or corrosion of the substrate surface, and the preparation success rate of multi-layer structures is low.
Design a functional gradient thermal protection coating, including an internal to external transition layer, a ceramic layer and a corrosion-resistant layer, which includes self-healing materials, ceramic materials and carbides, with an average particle size increasing gradients, and through automatic spraying technology A coating with uniform thickness and good interfacial compatibility is formed.
The high temperature stability and wear resistance of the substrate are achieved, the deformation and distortion of the coating system are reduced, the thermal protection performance and bonding strength are improved, the service life of the coating is extended, and the preparation success rate and efficiency are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal protection coatings, and in particular to a functional gradient thermal protection coating and an automatic forming method thereof. Background Art
[0002] With the rapid development of modern science and technology and industry, thermal protection materials are required to have different functional characteristics for different application backgrounds, and higher requirements are also placed on thermal protection materials. In recent years, a non-homogeneous gradient functional material has been developed that uses continuous or quasi-continuous changes in structure or composition to cause corresponding gradual changes in its performance. This type of gradient functional material mainly achieves gradient functional thermal protection by adopting different material structures or fiber gradient density structures. The different thermal stresses between different material structures in the former are prone to debonding defects between material interfaces, and the latter has a complex structural design and a long preparation cycle.
[0003] As a functional coating, thermal protective coatings have the characteristics of strong thermal stability, high thermal strength and excellent thermal protection performance (including thermal insulation performance, thermal shock resistance and thermal shock resistance) and have attracted widespread attention. However, during the service of existing single-layer thermal protective coatings, environmental corrosive media will penetrate through the surface pore structure and penetrate into the interface between the coating and the substrate. After a periodic erosion process, the substrate surface often exhibits severe oxidation or corrosion behavior. In addition, there is an inevitable problem of expansion, contraction and deformation inconsistency in the single-layer thermal protective coating system. Therefore, the realization of gradient functionalization application of coatings is of great significance for industrial mass production in aerospace and aerospace. However, at this stage, the preparation process parameters of thermal protective coatings with functional gradient multilayer structures are difficult to effectively control, resulting in a low success rate in the preparation of multilayer thermal protective coatings.
[0004] Therefore, there is an urgent need to design a functional gradient thermal protective coating with good interface compatibility, high bonding strength, excellent high-temperature stability and thermal protection performance to meet the use requirements of the service process. Summary of the invention
[0005] In response to one or more technical problems existing in the prior art, the present invention provides a functional gradient thermal protective coating and an automatic forming method thereof. The functional gradient thermal protective coating provided by the present invention has uniform thickness distribution of each layer, good interface compatibility and high bonding strength, and has excellent high temperature stability and thermal protection performance.
[0006] The present invention provides a functional gradient thermal protective coating, which comprises a transition layer, a ceramic layer and an anti-corrosion layer arranged in sequence from the inside to the outside; the transition layer comprises a self-healing material, the ceramic layer comprises a ceramic material, and the anti-corrosion layer comprises a carbide; the average particle sizes of the self-healing material, the ceramic material and the carbide increase in a gradient.
[0007] Preferably, the self-healing material is one or more of silicon carbide, silicon hexaboride, silicon dioxide, boron trioxide, and molybdenum disilicide;
[0008] The ceramic material is a zirconium-containing ceramic material, preferably one or more of zirconium disilicide, zirconium dioxide, zirconium diboride, and zirconium carbide; and / or
[0009] The carbide is one or more of tungsten carbide, chromium carbide, silicon carbide, zirconium carbide and molybdenum carbide.
[0010] Preferably, the average particle size of the self-healing material is 20 to 180 nm;
[0011] The average particle size of the ceramic material is 150 to 400 nm; and / or
[0012] The average particle size of the carbide is 300-800nm.
[0013] Preferably, the thickness of the transition layer is 3 to 4 mm;
[0014] The thickness of the ceramic layer is 2 to 3 mm; and / or
[0015] The thickness of the anti-corrosion layer is 1 to 2 mm.
[0016] The present invention also provides an automatic forming method of the functional gradient thermal protective coating according to the first aspect, the automatic forming method comprising the following steps:
[0017] The self-healing material, the ceramic material and the carbide are mixed with a solvent respectively to obtain a self-healing coating, a ceramic coating and an anti-corrosion coating;
[0018] Automatic spraying equipment is used to spray self-healing coating, ceramic coating and anti-corrosion coating on the surface of the porous substrate in sequence, and a gradient functional thermal protection coating including a transition layer, a ceramic layer and an anti-corrosion layer is automatically formed on the surface of the porous aerogel thermal protection material.
[0019] Preferably, in the self-healing coating, the mass ratio of the self-healing material to the solvent is 50-70:130-180;
[0020] In the ceramic coating, the mass ratio of the ceramic material to the solvent is 60-80:130-180; and / or
[0021] In the anti-corrosion coating, the mass ratio of the carbide to the solvent is 100-120:130-180
[0022] Preferably, the solvent is ethanol, water or an ethanol aqueous solution. Preferably, the mass ratio of ethanol to water in the ethanol aqueous solution is 30 to 80:100.
[0023] Preferably, the spraying distance is 100 to 300 mm, preferably 150 to 250 mm;
[0024] The spraying speed is 200-400 m / s, preferably 280-310 m / s; and / or
[0025] The spraying method is equidistant reciprocating spraying.
[0026] Preferably, the spraying is performed by atomizing spraying.
[0027] Preferably, the atomization pressure of the atomization spraying is 1 to 5 MPa, preferably 3 to 5 MPa;
[0028] The fan-shaped area of the atomized spray is 1 to 5 cm 2 , preferably 1 to 3 cm 2 ; and / or
[0029] The flow rate of the atomization spray is 2 to 5 g / L, preferably 2 to 3 g / L.
[0030] Compared with the prior art, the present invention has at least the following beneficial effects:
[0031] The transition layer in the functional gradient thermal protective coating provided by the present invention contains a self-healing material, which can achieve the bonding performance between the substrate and the coating, the ceramic layer contains a ceramic material, which can improve the high-temperature thermal stability of the substrate, and the anti-corrosion layer contains carbides, which can improve the wear resistance and corrosion resistance of the substrate, and can effectively improve the problem of environmental corrosive media penetrating through the pore structure of the coating to the surface of the substrate, resulting in serious oxidation or corrosion on the surface of the substrate. By regulating the material type and particle size of each layer, a continuous and smooth transition of the thermal physical performance parameters between each layer in the coating thickness direction can be achieved, which minimizes the deformation and imbalance of the coating system.
[0032] The functional gradient thermal protective coating provided by the present invention has uniform thickness distribution of each layer, good interface compatibility of each layer, high bonding strength, no defects such as holes and glue deficiency between the layers, no defects such as cracks on the coating surface, and has excellent high temperature stability and thermal protection performance.
[0033] The automatic forming method of the functional gradient thermal protective coating of the present invention realizes the continuous and smooth transition of the thermal physical performance parameters between each layer in the thickness direction of the coating, which can minimize the problem of deformation and imbalance of the coating system, and reduce the thermal stress of the material interface while ensuring the high-temperature stability of the thermal protective coating, thereby improving the bonding strength of the coating, improving the thermal protection performance of the coating, and extending the service life of the coating. The automatic forming method of the functional gradient thermal protective coating of the present invention can realize the stable and controllable preparation of the thermal protective coating, while achieving the purpose of reducing costs and increasing efficiency, greatly improving the success rate and efficiency of the preparation of the functional gradient thermal protective coating, and reducing labor costs. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] The present invention provides a functional gradient thermal protective coating, which comprises a transition layer, a ceramic layer and an anti-corrosion layer arranged in sequence from the inside to the outside; the transition layer comprises a self-healing material, the ceramic layer comprises a ceramic material, and the anti-corrosion layer comprises a carbide; the average particle sizes of the self-healing material, the ceramic material and the carbide increase in a gradient.
[0036] The transition layer in the functional gradient thermal protective coating provided by the present invention contains a self-healing material, which can achieve the bonding performance between the substrate and the coating, the ceramic layer contains a ceramic material, which can improve the high-temperature thermal stability of the substrate, and the anti-corrosion layer contains carbides, which can improve the wear resistance and corrosion resistance of the substrate, and can effectively improve the problem of environmental corrosive media penetrating through the pore structure of the coating to the surface of the substrate, resulting in serious oxidation or corrosion on the surface of the substrate. By regulating the material type and particle size of each layer, a continuous and smooth transition of the thermal physical performance parameters between each layer in the coating thickness direction can be achieved, which minimizes the deformation and imbalance of the coating system.
[0037] The functional gradient thermal protective coating provided by the present invention has uniform thickness distribution of each layer, good interface compatibility of each layer, high bonding strength, no defects such as holes and glue deficiency between the layers, no defects such as cracks on the coating surface, and has excellent high temperature stability and thermal protection performance.
[0038] According to some preferred embodiments, the self-healing material is one or more of silicon carbide, silicon hexaboride, silicon dioxide, boron trioxide, and molybdenum disilicide;
[0039] The ceramic material is a zirconium-containing ceramic material, preferably one or more of zirconium disilicide, zirconium dioxide, zirconium diboride, and zirconium carbide; and / or
[0040] The carbide is one or more of tungsten carbide, chromium carbide, silicon carbide, zirconium carbide and molybdenum carbide.
[0041] According to some preferred embodiments, the average particle size of the self-healing material is 20 to 180 nm (for example, 20 nm, 50 nm, 60 nm, 80 nm, 100 nm, 120 nm, 150 nm, 160 nm or 180 nm).
[0042] The average particle size of the ceramic material is 150 to 400 nm (for example, 150 nm, 180 nm, 200 nm, 250 nm, 280 nm, 300 nm, 320 nm, 350 nm, 380 nm or 400 nm).
[0043] According to some preferred embodiments, the average particle size of the carbide is 300-800 nm (for example, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm or 800 nm).
[0044] According to some preferred embodiments, the thickness of the transition layer is 3 to 4 mm (for example, 3 mm, 3.2 mm, 3.4 mm, 3.5 mm, 3.6 mm, 3.8 mm or 4 mm);
[0045] The thickness of the ceramic layer is 2 to 3 mm (for example, 2 mm, 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm or 3 mm); and / or
[0046] The thickness of the anti-corrosion layer is 1 to 2 mm (for example, 1 mm, 1.2 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.8 mm or 2 mm).
[0047] The thickness of each layer in the functional gradient thermal protective coating of the present invention is not limited to the above range, and can be adjusted according to actual use requirements. The thickness of each layer can be regulated by controlling the number of spraying. After each spraying, drying treatment is required before the next spraying.
[0048] The present invention also provides an automatic forming method of the functional gradient thermal protective coating according to the first aspect, the automatic forming method comprising the following steps:
[0049] The self-healing material, the ceramic material and the carbide are mixed with a solvent respectively to obtain a self-healing coating, a ceramic coating and an anti-corrosion coating;
[0050] Automatic spraying equipment is used to spray self-healing coating, ceramic coating and anti-corrosion coating on the surface of the porous substrate in sequence, and a gradient functional thermal protection coating including a transition layer, a ceramic layer and an anti-corrosion layer is automatically formed on the surface of the porous aerogel thermal protection material.
[0051] It should be noted that before spraying the coating, the substrate surface is pre-treated and the automatic spraying equipment is cleaned and debugged. The pre-treatment is: grinding the substrate surface.
[0052] The present invention uses automatic spraying equipment to first spray self-healing coating on the surface of the substrate to form a transition layer, thereby achieving adhesion between the substrate and the coating; then spray ceramic coating on the surface of the transition layer to form a ceramic layer, thereby improving the high-temperature thermal stability of the substrate; finally, spray anti-corrosion coating on the surface of the ceramic layer to form an anti-corrosion layer, thereby improving the wear resistance and corrosion resistance of the substrate, and can effectively improve the problem of environmental corrosive media penetrating through the pore structure of the coating to the surface of the substrate, resulting in serious oxidation or corrosion on the surface of the substrate.
[0053] The automatic forming method of the functional gradient thermal protective coating of the present invention realizes the continuous and smooth transition of the thermal physical performance parameters between each layer in the thickness direction of the coating, which can minimize the problem of deformation and imbalance of the coating system, and reduce the thermal stress of the material interface while ensuring the high-temperature stability of the thermal protective coating, thereby improving the bonding strength of the coating, improving the thermal protection performance of the coating, and extending the service life of the coating. The automatic forming method of the functional gradient thermal protective coating of the present invention can realize the stable and controllable preparation of the thermal protective coating, while achieving the purpose of reducing costs and increasing efficiency, greatly improving the success rate and efficiency of the preparation of the functional gradient thermal protective coating, and reducing labor costs.
[0054] The particle sizes of the self-healing material, ceramic material and carbide in the self-healing coating, ceramic coating and anti-corrosion coating of the present invention increase gradually, which can ensure that the depth of each coating entering the porous matrix decreases gradually, thereby obtaining a thermal protection coating with a functional gradient. The present invention can control the depth of each coating entering the porous matrix by controlling the particle sizes of the self-healing material, ceramic material and carbide according to specific use requirements.
[0055] According to some preferred embodiments, in the self-healing coating, the mass ratio of the self-healing material to the solvent is 50-70:130-180.
[0056] According to some preferred embodiments, in the ceramic coating, the mass ratio of the ceramic material to the solvent is 60-80:130-180.
[0057] According to some preferred embodiments, in the anti-corrosion coating, the mass ratio of the carbide to the solvent is 100-120:130-180.
[0058] According to some preferred embodiments, the solvent is ethanol, water or an ethanol aqueous solution. Preferably, the mass ratio of ethanol to water in the ethanol aqueous solution is 30 to 80:100.
[0059] According to some preferred embodiments, the spraying distance is 100-300 mm (for example, 100 mm, 150 mm, 200 mm, 250 mm or 300 mm), preferably 150-250 mm (for example, 150 mm, 180 mm, 200 mm, 230 mm or 250 mm);
[0060] The spraying speed is 200-400 m / s (for example, 200 m / s, 220 m / s, 250 m / s, 280 m / s, 300 m / s, 320 m / s, 350 m / s, 380 m / s or 400 m / s), preferably 280-310 m / s (for example, 280 m / s, 290 m / s, 300 m / s or 310 m / s); and / or
[0061] The spraying method is equidistant reciprocating spraying.
[0062] According to some preferred embodiments, the spraying is performed by atomized spraying.
[0063] According to some preferred embodiments, the atomization pressure of the atomization spraying is 1 to 5 MPa (for example, 1 MPa, 2 MPa, 3 MPa, 4 MPa or 5 MPa), preferably 3 to 5 MPa;
[0064] The fan-shaped area of the atomized spray is 1 to 5 cm 2 (For example, it can be 1cm 2 , 2cm 2 , 3cm 2 , 4cm 2 or 5cm 2 ), preferably 1 to 3 cm 2 ; and / or
[0065] The flow rate of the atomized spray is 2 to 5 g / L (for example, 2 g / L, 3 g / L, 4 g / L or 5 g / L), preferably 2 to 3 g / L.
[0066] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.
[0067] Example 1
[0068] (1) Grinding the surface of the porous aerogel thermal protection material with sandpaper, clamping and fixing the porous aerogel material on a trolley, operating the system control cabinet to complete the debugging of the automatic spraying equipment before work, injecting the cleaning solvent into the cleaning bucket, and completing the cleaning of the connecting pipes and the robot; wherein the cleaning solvent is a mixed solution of ethanol and water, wherein the mass ratio of ethanol to water is 50:100.
[0069] (2) A self-healing material (silicon carbide powder with an average particle size of 100 nm) is mixed with a solvent to obtain a self-healing coating, wherein the mass ratio of the self-healing material to the solvent is 60:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); a ceramic material (zirconium disilicide powder with an average particle size of 280 nm) is mixed with a solvent to obtain a ceramic coating, wherein the mass ratio of the ceramic material to the solvent is 70:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); a carbide (tungsten carbide powder with an average particle size of 750 nm) is mixed with a solvent to obtain an anti-corrosion coating, wherein the mass ratio of the carbide material to the solvent is 110:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); and the self-healing coating, ceramic coating and anti-corrosion coating are respectively injected into feed barrels I, II and III, and the spraying flow rate is set to 3 g / L and the fan area is 3 cm 2 , the atomization pressure is 5MPa.
[0070] (3) The workpiece is transported through the robot control cabinet, and the corresponding spraying program is designed. The spraying distance is set to 150 mm, the spray gun speed is set to 300 m / s, and the spraying trajectory is set to equidistant circular spraying and other parameter values. The feed barrels I, II, and III are opened in sequence for automatic spraying. A transition layer (average thickness of 3.5 mm), a ceramic layer (average thickness of 2.4 mm), and an anti-corrosion layer (average thickness of 1.6 mm) are sprayed in sequence. After each layer is sprayed, it is dried at room temperature before the next layer is sprayed. Finally, the automatic forming of the gradient functional thermal protective coating on the surface of the porous aerogel thermal protective material is completed.
[0071] The present invention focuses on observing the thickness of the transition layer in the spray intersection area and finds that the thickness of the transition layer is evenly distributed and there is no residual coating on the surface, indicating that the self-healing coating has good permeability; the ceramic layer coating is evenly distributed, and there is no cracking or glue leakage on the surface after spraying, and there are no holes or glue shortages between the transition layer and the ceramic layer, indicating that the interface compatibility between the transition layer and the ceramic layer is good; the anti-corrosion layer is evenly distributed.
[0072] The flat-plate-level porous aerogel thermal protection material with a gradient functional thermal protection coating formed on the surface prepared in this embodiment was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). Compared with the porous aerogel thermal protection material without the gradient functional thermal protection coating sprayed, the linear shrinkage of the porous aerogel thermal protection material sprayed with the gradient thermal protection coating was reduced by 30% after the temperature resistance test. After the tensile test, the coating was intact and the failure position occurred in the non-coating area, indicating that the prepared gradient functional thermal protection coating has good interface compatibility between layers and the bonding strength is higher than the self-strength of the matrix material.
[0073] Example 2
[0074] (1) Grinding the surface of the porous aerogel thermal protection material with sandpaper, clamping and fixing the porous aerogel material on a trolley, operating the system control cabinet to complete the debugging of the automatic spraying equipment before work, injecting the cleaning solvent into the cleaning bucket, and completing the cleaning of the connecting pipes and the robot; wherein the cleaning solvent is a mixed solution of ethanol and water, wherein the mass ratio of ethanol to water is 50:100.
[0075] (2) A self-healing material (silicon hexaboride powder with an average particle size of 150 nm) is mixed with a solvent to obtain a self-healing coating, wherein the mass ratio of the self-healing material to the solvent is 60:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); a ceramic material (zirconium dioxide powder with an average particle size of 320 nm) is mixed with a solvent to obtain a ceramic coating, wherein the mass ratio of the ceramic material to the solvent is 70:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); a carbide (chromium carbide powder with an average particle size of 790 nm) is mixed with a solvent to obtain an anti-corrosion coating, wherein the mass ratio of the carbide material to the solvent is 110:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); and the self-healing coating, ceramic coating and anti-corrosion coating are respectively injected into feed barrels I, II and III, and the spraying flow rate is set to 3 g / L and the fan area is 3 cm 2 , the atomization pressure is 5MPa.
[0076] (3) The workpiece is transported through the robot control cabinet, and the corresponding spraying program is designed. The spraying distance is set to 150 mm, the spray gun speed is set to 300 m / s, and the spraying trajectory is set to equidistant circular spraying and other parameter values. The feed barrels I, II, and III are opened in sequence for automatic spraying. A transition layer (average thickness of 3.8 mm), a ceramic layer (average thickness of 2.6 mm), and an anti-corrosion layer (average thickness of 1.9 mm) are sprayed in sequence. After each layer is sprayed, it is dried at room temperature before the next layer is sprayed. Finally, the automatic forming of the gradient functional thermal protective coating on the surface of the porous aerogel thermal protective material is completed.
[0077] The present invention focuses on observing the thickness of the transition layer in the spray intersection area and finds that the thickness of the transition layer is evenly distributed and there is no residual coating on the surface, indicating that the self-healing coating has good permeability; the ceramic layer coating is evenly distributed, and there is no cracking or glue leakage on the surface after spraying, and there are no holes or glue shortages between the transition layer and the ceramic layer, indicating that the interface compatibility between the transition layer and the ceramic layer is good; the anti-corrosion layer is evenly distributed.
[0078] The flat-plate-level porous aerogel thermal protection material with a gradient functional thermal protection coating formed on the surface prepared in this embodiment was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). Compared with the porous aerogel thermal protection material without the gradient functional thermal protection coating sprayed, the linear shrinkage of the porous aerogel thermal protection material sprayed with the gradient thermal protection coating was reduced by 33% after the temperature resistance test. After the tensile test, the coating was intact and the damage position occurred in the non-coating area, indicating that the prepared gradient functional thermal protection coating has good interface compatibility between layers and the bonding strength is higher than the self-strength of the matrix material.
[0079] Example 3
[0080] (1) Grinding the surface of the porous aerogel thermal protection material with sandpaper, clamping and fixing the porous aerogel material on a trolley, operating the system control cabinet to complete the debugging of the automatic spraying equipment before work, injecting the cleaning solvent into the cleaning bucket, and completing the cleaning of the connecting pipes and the robot; wherein the cleaning solvent is a mixed solution of ethanol and water, wherein the mass ratio of ethanol to water is 50:100.
[0081] (2) A self-healing material (silicon carbide powder with an average particle size of 100 nm) is mixed with a solvent to obtain a self-healing coating, wherein the mass ratio of the self-healing material to the solvent is 60:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); a ceramic material (zirconium disilicide powder with an average particle size of 280 nm) is mixed with a solvent to obtain a ceramic coating, wherein the mass ratio of the ceramic material to the solvent is 70:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); a carbide (tungsten carbide powder with an average particle size of 750 nm) is mixed with a solvent to obtain an anti-corrosion coating, wherein the mass ratio of the carbide material to the solvent is 110:150, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 50:100); and the self-healing coating, ceramic coating and anti-corrosion coating are respectively injected into feed barrels I, II and III, and the spraying flow rate is set to 3 g / L and the fan area is 3 cm 2 , the atomization pressure is 3MPa.
[0082] (3) The workpiece is transported through the robot control cabinet, and the corresponding spraying program is designed. The spraying distance is set to 200 mm, the spray gun speed is set to 280 m / s, and the spraying trajectory is set to equidistant circular spraying and other parameter values. The feed barrels I, II, and III are opened in sequence for automatic spraying. A transition layer (average thickness of 3.6 mm), a ceramic layer (average thickness of 2.4 mm), and an anti-corrosion layer (average thickness of 1.7 mm) are sprayed in sequence. After each layer is sprayed, it is dried at room temperature before the next layer is sprayed. Finally, the automatic forming of the gradient functional thermal protective coating on the surface of the porous aerogel thermal protective material is completed.
[0083] The present invention focuses on observing the thickness of the transition layer in the spray intersection area and finds that the thickness of the transition layer is evenly distributed and there is no residual coating on the surface, indicating that the self-healing coating has good permeability; the ceramic layer coating is evenly distributed, and there is no cracking or glue leakage on the surface after spraying, and there are no holes or glue shortages between the transition layer and the ceramic layer, indicating that the interface compatibility between the transition layer and the ceramic layer is good; the anti-corrosion layer is evenly distributed.
[0084] The flat-plate-level porous aerogel thermal protection material with a gradient functional thermal protection coating formed on the surface prepared in this embodiment was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). Compared with the porous aerogel thermal protection material without the gradient functional thermal protection coating sprayed, the linear shrinkage of the porous aerogel thermal protection material sprayed with the gradient thermal protection coating was reduced by 32% after the temperature resistance test. After the tensile test, the coating was intact and the failure position occurred in the non-coating area, indicating that the prepared gradient functional thermal protection coating has good interface compatibility between layers and the bonding strength is higher than the self-strength of the matrix material.
[0085] Example 4
[0086] (1) Grinding the surface of the porous aerogel thermal protection material with sandpaper, clamping and fixing the porous aerogel material on a trolley, operating the system control cabinet to complete the debugging of the automatic spraying equipment before work, injecting the cleaning solvent into the cleaning bucket, and completing the cleaning of the connecting pipes and the robot; wherein the cleaning solvent is a mixed solution of ethanol and water, wherein the mass ratio of ethanol to water is 50:100.
[0087] (2) A self-healing material (silicon carbide powder with an average particle size of 100 nm) is mixed with a solvent to obtain a self-healing coating, wherein the mass ratio of the self-healing material to the solvent is 50:170, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 70:100); a ceramic material (zirconium disilicide powder with an average particle size of 280 nm) is mixed with a solvent to obtain a ceramic coating, wherein the mass ratio of the ceramic material to the solvent is 60:170, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 70:100); a carbide (tungsten carbide powder with an average particle size of 750 nm) is mixed with a solvent to obtain an anti-corrosion coating, wherein the mass ratio of the carbide material to the solvent is 100:170, and the solvent is an ethanol aqueous solution (the mass ratio of ethanol to water is 70:100); and the self-healing coating, ceramic coating and anti-corrosion coating are respectively injected into feed barrels I, II and III, and the spraying flow rate is set to 3 g / L and the fan area is 3 cm 2 , the atomization pressure is 5MPa.
[0088] (3) The workpiece is transported by the robot control cabinet, and the corresponding spraying program is designed. The spraying distance is set to 150 mm, the spray gun speed is set to 300 m / s, and the spraying trajectory is set to equidistant circular spraying and other parameter values. The feed barrels I, II, and III are opened in sequence for automatic spraying. Since the concentration of the configured gradient coating is lower than that in Example 1, in order to ensure that the thickness range of the thermal protective coating meets the product requirements, the number of spraying of each layer of coating is increased, and the transition layer (average thickness is 3.3 mm), the ceramic layer (average thickness is 2.3 mm) and the anti-corrosion layer (average thickness is 1.3 mm) are sprayed in sequence. After each layer is sprayed, it is dried at room temperature before the next layer is sprayed, and finally the automatic forming of the gradient functional thermal protective coating on the surface of the porous aerogel thermal protective material is completed.
[0089] The present invention focuses on observing the thickness of the transition layer in the spray intersection area and finds that the thickness of the transition layer is evenly distributed and there is no residual coating on the surface, indicating that the self-healing coating has good permeability; the ceramic layer coating is evenly distributed, and there is no cracking or glue leakage on the surface after spraying, and there are no holes or glue shortages between the transition layer and the ceramic layer, indicating that the interface compatibility between the transition layer and the ceramic layer is good; the anti-corrosion layer is evenly distributed.
[0090] The flat-plate-level porous aerogel thermal protection material with a gradient functional thermal protection coating formed on the surface prepared in this embodiment was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). Compared with the porous aerogel thermal protection material without the gradient functional thermal protection coating sprayed, the linear shrinkage of the porous aerogel thermal protection material sprayed with the gradient thermal protection coating was reduced by 27% after the temperature resistance test. After the tensile test, the coating was intact and the failure position occurred in the non-coating area, indicating that the prepared gradient functional thermal protection coating has good interface compatibility between layers and the bonding strength is higher than the self-strength of the matrix material.
[0091] Comparative Example 1
[0092] It is basically the same as Example 1, except that in step (2), the self-healing material is silicon carbide powder with an average particle size of 10 nm, the ceramic material is zirconium disilicide powder with an average particle size of 10 nm, and the carbide is tungsten carbide powder with an average particle size of 10 nm.
[0093] The transition layer, ceramic layer and anti-corrosion layer in the functional gradient thermal protection coating prepared in this comparative example diffuse more seriously in the thickness direction, and the coating thickness diffuses to the entire porous aerogel thermal protection material matrix. The coating density is uneven, the surface coating is not dense and there are cracks;
[0094] The flat-plate-level porous aerogel thermal protection material with a gradient functional thermal protection coating formed on the surface prepared in this comparative example was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). After the temperature resistance test, cracks appeared in the thermal protection material, and the cracks appeared in the loose coating area. After the tensile test, the coating area was damaged, and the damage position occurred in the loose coating area.
[0095] Comparative Example 2
[0096] It is basically the same as Example 1, except that in step (2), the self-healing material is silicon carbide powder with an average particle size of 100 nm, the ceramic material is zirconium disilicide powder with an average particle size of 720 nm, and the carbide is tungsten carbide powder with an average particle size of 750 nm.
[0097] The present invention focuses on observing the coating thickness in the spray intersection area and finds that the coating is evenly distributed and there is no residual coating on the surface, indicating that the self-healing coating has good permeability; the average thickness of the prepared ceramic layer is 4.3 mm, and the ceramic layer is relatively evenly distributed. However, the ceramic coating has poor permeability, and glue penetration defects appear on the surface after spraying, and more cracks appear between the transition layer and the ceramic layer; the anti-corrosion layer is relatively evenly distributed.
[0098] The flat-plate-level porous aerogel thermal protection material with a surface-formed gradient functional thermal protection coating prepared in this comparative example was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). After the temperature resistance test, cracks appeared in the thermal protection material, and the cracks appeared in the loose coating area. After the tensile test, the coating area was damaged, and the damage occurred in the loose ceramic layer area.
[0099] Comparative Example 3
[0100] The same as Example 3, except that the spray flow rate is set to 6 g / L and the fan area is set to 6 cm 2 , the atomization pressure is 1MPa.
[0101] The coating distribution of the functional gradient thermal protection coating prepared in this comparative example is extremely dispersed, the coating thickness is seriously uneven, many holes and glue shortages appear at the interface between the transition layer and the ceramic layer, and glue leakage and cracking areas appear on the surface of the product.
[0102] The flat-plate-level porous aerogel thermal protection material with a gradient functional thermal protection coating formed on the surface prepared in this comparative example was subjected to a temperature resistance test (performed in accordance with GJB 323B-2018 standard) and a thickness direction tensile test (performed in accordance with GB / T1452-2018 standard). After the temperature resistance test, cracks appeared in the thermal protection material, and the cracks appeared in the loose coating area. After the tensile test, the coating area was damaged, and the damage position occurred in the loose coating area.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A functionally gradient thermal protective coating, characterized in that: The functional gradient thermal protection coating includes a transition layer, a ceramic layer and an anti-corrosion layer arranged in sequence from the inside to the outside; the transition layer contains a self-healing material, the ceramic layer contains a ceramic material, and the anti-corrosion layer contains a carbide; the average particle sizes of the self-healing material, the ceramic material and the carbide increase in a gradient.
2. The functionally gradient thermal protective coating according to claim 1, characterized in that: The self-healing material is one or more of silicon carbide, silicon hexaboride, silicon dioxide, boron trioxide, and molybdenum disilicide; The ceramic material is a zirconium-containing ceramic material, preferably one or more of zirconium disilicide, zirconium dioxide, zirconium diboride, and zirconium carbide; and / or The carbide is one or more of tungsten carbide, chromium carbide, silicon carbide, zirconium carbide and molybdenum carbide.
3. The functionally gradient thermal protective coating according to claim 1, characterized in that: The average particle size of the self-healing material is 20 to 180 nm; The average particle size of the ceramic material is 150 to 400 nm; and / or The average particle size of the carbide is 300-800nm.
4. The functionally gradient thermal protective coating according to claim 1, characterized in that: The thickness of the transition layer is 3 to 4 mm; The thickness of the ceramic layer is 2 to 3 mm; and / or The thickness of the anti-corrosion layer is 1 to 2 mm.
5. An automatic forming method for a functional gradient thermal protective coating according to any one of claims 1 to 4, characterized in that: The automatic forming method comprises the following steps: The self-healing material, the ceramic material and the carbide are mixed with a solvent respectively to obtain a self-healing coating, a ceramic coating and an anti-corrosion coating; Automatic spraying equipment is used to spray self-healing coating, ceramic coating and anti-corrosion coating on the surface of the porous substrate in sequence, and a gradient functional thermal protection coating including a transition layer, a ceramic layer and an anti-corrosion layer is automatically formed on the surface of the porous aerogel thermal protection material.
6. The automatic forming method according to claim 5, characterized in that: In the self-healing coating, the mass ratio of the self-healing material to the solvent is 50-70:130-180; In the ceramic coating, the mass ratio of the ceramic material to the solvent is 60-80:130-180; and / or In the anti-corrosion coating, the mass ratio of the carbide to the solvent is 100-120:130-180.
7. The automatic forming method according to claim 5, characterized in that: The solvent is ethanol, water or ethanol aqueous solution. Preferably, the mass ratio of ethanol to water in the ethanol aqueous solution is 30-80:
100.
8. The automatic forming method according to claim 5, characterized in that: The spraying distance is 100 to 300 mm, preferably 150 to 250 mm; The spraying speed is 200-400 m / s, preferably 280-310 m / s; and / or The spraying method is equidistant reciprocating spraying.
9. The automatic forming method according to claim 5, characterized in that: The spraying adopts atomization spraying.
10. The automatic forming method according to claim 9, characterized in that: The atomization pressure of the atomization spraying is 1 to 5 MPa, preferably 3 to 5 MPa; The fan-shaped area of the atomized spray is 1 to 5 cm 2 , preferably 1 to 3 cm 2 ; and / or The flow rate of the atomization spray is 2 to 5 g / L, preferably 2 to 3 g / L.
